FORMING OF THE MODEL SIGNAL IN DEVICE USED TO RECOGNITION OF GROUND MOVING OBJECTS - V. V. Siutsevich; A. E. Vinogradov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
For detection and recognition of ground moving objects with seismic devices it's nesessary to form the model of seismic signals, corresponding of each object class. Unknown moment of seismic wave incoming and it's time parameters demand to building of multichannel scheme etalon signals generator.